Therapeutic Strategies in the Management of COVID-19 - Naik, Rajashri R.; Shakya, Ashok K. (Frontiers in Molecular Biosciences, 2021)
Since December 2019, SARS COV 2 (COVID-19), novel corona virus has caused pandemic globally, with rise in the number of cases and death of the patients. Vast majority of the countries that are dealing with rise in the active cases and death of patients suffering from novel corona viruses COVID-19 are trying to content the virus by isolating the patients and treating them with the approved antiviral that have been previously used in treating SARS, MERS, and drugs that are used to treat other viral infections. Some of these are under clinical trials. At present there are no therapeutically effective antiviral present and there are no vaccines or drugs available that are clinically approved for treating the corona virus. The current strategy is to re-purpose the available drugs or antiviral that can minimize or reduce the burden of the health care emergencies. In this article the reuse of antiviral, US-FDA approved drugs, plant based therapeutic, anti-malarial, anti-parasitic, anti–HIV drugs and the traditional medicines that are being currently used in treating the symptoms of COVID–19 patients is discussed emphasis is also given on the treatment using monoclonal antibodies. This articles provides the therapeutic strategies that qualify as one of the best available treatment for the better management of the COVID – 19 patients in order to achieve medical benefits.